The Roles of RANK/RANKL/OPG in Cardiac, Skeletal, and Smooth Muscles in Health and Disease - Marcadet, Laetitia; Bouredji, Zineb; Argaw, Anteneh; Frenette, Jérôme (Frontiers in Cell and Developmental Biology, 2022)
Although their physiology and functions are very different, bones, skeletal and smooth muscles, as well as the heart have the same embryonic origin. Skeletal muscles and bones interact with each other to enable breathing, kinesis, and the maintenance of posture. Often, muscle and bone tissues degenerate synchronously under various conditions such as cancers, space travel, aging, prolonged bed rest, and neuromuscular diseases. In addition, bone tissue, skeletal and smooth muscles, and the heart share common signaling pathways. The RANK/RANKL/OPG pathway, which is essential for bone homeostasis, is also implicated in various physiological processes such as sarcopenia, atherosclerosis, and cardiovascular diseases. Several studies have reported bone-skeletal muscle crosstalk through the RANK/RANKL/OPG pathway. This review will summarize the current evidence indicating that the RANK/RANKL/OPG pathway is involved in muscle function. First, we will briefly discuss the role this pathway plays in bone homeostasis. Then, we will present results from various sources indicating that it plays a physiopathological role in skeletal, smooth muscle, and cardiac functions. Understanding how the RANK/RANKL/OPG pathway interferes in several physiological disorders may lead to new therapeutic approaches aimed at protecting bones and other tissues with a single treatment.